Function of the Type IV pili proteins in the cyanobacterium Synechocystis sp. PCC 6803. - Linhartová, Markéta (Jihočeská univerzita, 2021)
The thesis is focused on the function of the Type IV pili machinery in the cyanobacterium Synechocystis sp. PCC. 6803. In my work, I provided evidence that in phototrophs, some pilin proteins have acquired a novel function related to metal transport and assembly of photosynthetic complexes. The tight connection between the synthesis of the major pilin PilA1 and the biogenesis of photosynthetic complexes has been demonstrated in the pilD mutant lacking prepilins peptidase. I isolated and characterized pilD suppressor strains, which revealed the important role of the minor pilin PilA2 in the glycosylation of PilA1 and the restricted mobility of PilA1 prepilin in the membrane. My unpublished data indicate that the retraction mode of pili, driven by the PilT1 molecular motor, facilitates manganese uptake and the activity of this machine is critically important during the regulation from the exponential to the linear growth phase.
Function of the Type IV pili proteins in the cyanobacterium Synechocystis sp. PCC 6803.
Ph.D. Thesis
Keywords: type IV pili; Synechocystis; photosystem II; PilD peptidase; major pilin; prepilin toxicity; photoautotrophy; metal transport; type IV pili; Synechocystis; photosystem II; PilD peptidase; major pilin; prepilin toxicity; photoautotrophy; metal transport